Phloem Girdling of Norway Spruce Alters Quantity and Quality of Wood Formation in Roots Particularly Under Drought - Rainer-Lethaus, Gina; Oberhuber, Walter (Frontiers in Plant Science, 2018)
Carbon (C) availability plays an essential role in tree growth and wood formation. We evaluated the hypothesis that a decrease in C availability (i) triggers mobilization of C reserves in the coarse roots of Picea abies to maintain growth and (ii) causes modification of wood structure notably under drought. Six-year-old saplings were subjected to two levels of soil moisture (watered versus drought conditions) and root C status was manipulated by physically blocking phloem transport in the stem at three girdling dates (GD). Stem girdling was done before the onset of bud break (day of the year [doy] 77), during vigorous aboveground shoot and radial stem growth (GD doy 138), and after cessation of shoot growth (GD doy 190). The effect of blockage of C transport on root growth, root phenology and wood anatomical traits (cell lumen diameter (CLD) and cell wall thickness (CWT)) in earlywood (EW) and latewood (LW) was determined. To evaluate changes in belowground C status caused by girdling, non-structural carbohydrates (NSC; soluble sugars and starch) in coarse roots were determined at the time of girdling and after the growing season. Although fine root mass significantly decreased in response to blockage of phloem C transport, the phenology of root elongation growth was not affected. Surprisingly, radial root growth and CLD of EW tracheids in coarse roots were strikingly increased in drought-stressed trees, when girdling occurred before bud break or during aboveground stem growth. In watered trees, the growth response to girdling was less distinct, but the CWT of EW significantly increased. Starch reserves in the roots of girdled trees significantly decreased in both soil moisture treatments and at all GDs. We conclude that (i) radial growth and wood development in coarse roots of P. abies saplings are not only dependent on current photosynthates, and (ii) blockage of phloem transport induces physiological changes that outweigh drought effects imposed on root cambial activity and cell differentiation.